Moonlighting Behaviour among Migrants: Determinants and Implication For Wellbeing in South Africa - Quarshie, Emmanuel; Alagidede, Imhotep Paul; Duodu, Albert; Sosi, Edwin Teye (African Human Mobility Review, 2022)
Notwithstanding the wealth of research on migration and subjective wellbeing, the issue of moonlighting and its welfare implication among migrants has no traces in the empirical literature. Using the rich individual-level panel data from the National Income Dynamic Survey (NIDS), this study established a number of interesting findings: (a) there is moonlighting among international migrants; (b) hours spent on the primary job and financial motive, amongst other socio-demographic factors are key predictors of moonlighting (c) international migrants are more likely to have more than one job, very often to meet contingencies, but mostly to help smoothen consumption over the life cycle; (d) individuals who spend more hours on their primary job are less likely to moonlight. Regarding wellbeing and happiness, it is evident that moonlighting and hours spent on primary jobs negatively influence self-reported wellbeing and happiness. Given the ravaging effects of COVID-19, a better understanding of the post-pandemic migration trajectory, job search strategies, economic activities among migrants, with a specific focus on moonlighting and its implication on wellbeing, is essential to national and international policy rethinking in order to achieve a triple win for the migrant, the host and origin countries.